Intensity and Prevalence of Ectoparasites in Tilapia (Oreochromis niloticus) from Floating Net Cages in Lake Batur, Bali - Yogi, Gusti Ayu Putu Cintya Pratami; Julyantoro, Pande Gde Sasmita; Pebriani, Dewa Ayu Angga; Sudaryatma, Putu Eka (Aquaculture Department, University of Mataram, 2025)
Tilapia (Oreochromis niloticus) is one of the most cultivated freshwater fish. The problem that is often faced in fish farming is diseases caused by parasitic attacks (ectoparasites) which can cause a decrease in fish production levels. To overcome these problems, research is needed on the intensity and prevalence of ectoparasites in tilapia (Oreochromis niloticus) to determine the density of ectoparasite attacks and the percentage of ectoparasites in tilapia. Tilapia (Oreochromis niloticus) samples were taken from the Floating Net Cage (KJA) of Lake Batur, Songan Village, Kedisan and Trunyan. Sampling is carried out by purposive sampling or determining location points. The tilapia (Oreochromis niloticus) samples examined were 36 fish samples with a size of 14.7-21 cm tilapia niwana. The ectoparasite found only in the gills of tilapia, namely Dactylogyrus sp. (506 ind) and Gyrodactylus sp. (13 ind). The highest intensity in the genus Dactylogyrus was 14.06 ind/head in the medium category, while in the genus Gyrodactylus it was 1.86 ind/head in the low category. The highest prevalence value in the genus Dactylogyrus is 100% with the always category while for the genus Gyrodactylus is 19.44% with the frequent category. The data supporting water quality in this study includes temperature, pH, and DO. The temperature of lake water in floating net cages during the study ranged from 23oC-28oC, pH or acidity degree ranged from 8.1-9 and DO range from 4.8-5.6 mg/L. The results of the water quality in this study are classified as optimal for tilapia rearing.